2018
DOI: 10.1002/jum.14797
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Large‐Sample Shear Wave Ultrasound Elastographic Study of the Achilles Tendon in Chinese Adults

Abstract: The Young modulus of the Achilles tendon as measured by shear wave elastography is related to body weight as well as the perimeter or thickness of the tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…The averaged value of Young's modulus for the tested samples was equal to 264.78 ± 55.11 MPa (Table 1) that is comparable with the values reported in (Chen et al, 2013). The values of the elastic modulus reported in literature are between 374.24 kPa (Cao et al, 2018) and 2.0 GPa (Kongsgaard et al, 2011) and depend on e.g. the cadaver age type of study (Kongsgaard et al, 2011) and strain rate (Wren et al, 2001).…”
Section: Resultssupporting
confidence: 80%
“…The averaged value of Young's modulus for the tested samples was equal to 264.78 ± 55.11 MPa (Table 1) that is comparable with the values reported in (Chen et al, 2013). The values of the elastic modulus reported in literature are between 374.24 kPa (Cao et al, 2018) and 2.0 GPa (Kongsgaard et al, 2011) and depend on e.g. the cadaver age type of study (Kongsgaard et al, 2011) and strain rate (Wren et al, 2001).…”
Section: Resultssupporting
confidence: 80%
“…One of the major drawbacks of shear wave imaging is that it can result in saturation of the elastogram in ankle positions around 0° of flexion since the Achilles tendon bears high tensile loads in this position or when dorsiflexed. Given this limitation, authors [ 38 ] of previous research suggested that the evaluation of AT should be limited to a relaxed or plantar flexed position and not stretched or loaded tendon with additional weight as this will increase the shear wave velocity [ 39 , 57 ] leading to saturation and possibly false results.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for normal SWE values in Achilles tendon were taken by following two previous multicenter studies. 40 41 These studies calculated the mean elasticity of normal Achilles tendon to be >300kPa.…”
Section: Methodsmentioning
confidence: 99%